Genetic detection and characterization of emerging HoBi-like viruses in archival foetal bovine serum batches. Issue 4 (July 2015) - Giammarioli, M.; Ridpath, J.F.; Rossi, E.; Bazzucchi, M.; Casciari, C.; De Mia, G.M.
Abstract Bovine viral diarrhea viruses (BVDV) are members of the Pestivirus genus within the family Flaviviridae. Based on antigenic and nucleotide differences, BVDV are classified into two recognized species, BVDV-1 and BVDV-2. More recently, a new putative pestivirus species, tentatively called "HoBi-like", has been associated with bovine viral diarrhea. HoBi-like viruses were first identified in fetal bovine serum (FBS) imported from Brazil. Subsequently, a number of HoBi-like viruses have been detected as contaminants in FBS or cell culture and in live ruminants. To further investigate the possible pestivirus contamination in commercially available FBS batches, 26 batches of FBS with various countries of origin, were tested in this study for the presence of bovine pestiviruses. All the 26 batches were positive by RT-PCR for at least one species of bovine pestiviruses. HoBi-like viruses were detected in 15 batches. Analysis of the 5′UTR and Npro sequences of 15 newly identified HoBi-like viruses combined with analysis of additional sequences from GenBank, identified 4 genetic groups tentatively named 3a–3d. The current study confirmed the presence of the emerging HoBi-like viruses in FBS products labeled with different geographic origins. This finding has obvious implications for the safety of biological products, such cell lines and vaccines.